Les femmes juives et leurs maisons : de l’habitat au foyer (Couronne d’Aragon, XIVe siècle) - Chloé Bonnet (Genre & Histoire)
The daily life of Jewish women and men is well documented in the registers of Christian notaries in fourteenth-century Catalonia. Medieval Jewish women lived in homes very similar to those of Christian women. Whether these dwellings took the form of an entire house or were reduced to a single room, their home was the place where they managed their family and sometimes carried on an artisanal activity. Jewish women also played an important role in the urban real estate market, whether buying and selling property or renting. The mirroring effect of the different facets of Jewish women inside and outside their homes raises questions about the intersectional position of these women in the urban societies of the medieval Mediterranean. The question here will be to understand how women appropriated their living spaces to make them into homes.